1984
DOI: 10.1159/000457153
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Triiodothyronine and Dexamethasone on Male and Female Fetal Rat Lung Surfactant Synthesis

Abstract: It has previously been reported that morphologic and functional indices of fetal lung maturation are delayed in male rabbit fetuses, and these differences cannot be overcome by glucocorticoid treatment. Since thyroid hormone also stimulates surfactant production we have studied the effects of triiodothyronine (T(3)) and dexamethasone on saturated phosphatidylcholine (SPC) synthesis by day 20 male and female rat lung. Control male lung slices incorporated significantly less ^3H-choline into SPC than females; su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 11 publications
3
14
1
Order By: Relevance
“…Thyroidectomy of fetal sheep reduces the number of type II pneumocytes in the lungs at term as well as the number of surfactantcontaining lamellar bodies in these cells (Ayromlooi et al 1983). In vitro and in vivo studies have shown that thyroid hormones affect synthesis of both the phospholipid and protein components of surfactant in fetal mice, rats, sheep, monkeys, and human infants (Ballard et al 1984, Das et al 1984, Torday & Dow 1984, Warburton et al 1988, Romaguera et al 1993, Gilbert et al 2001, van Tuyl et al 2004. In particular, thyroid hormones promote synthesis of surfactant proteins B and C. They also increase the phospholipid content of lung liquid, although this effect may be mediated via upregulation of pulmonary b-adrenergic receptor expression and, hence, enhanced epinephrine-stimulated surfactant release (Das et al 1984, Warburton et al 1988.…”
Section: The Lungs and Respiratory Functionmentioning
confidence: 99%
“…Thyroidectomy of fetal sheep reduces the number of type II pneumocytes in the lungs at term as well as the number of surfactantcontaining lamellar bodies in these cells (Ayromlooi et al 1983). In vitro and in vivo studies have shown that thyroid hormones affect synthesis of both the phospholipid and protein components of surfactant in fetal mice, rats, sheep, monkeys, and human infants (Ballard et al 1984, Das et al 1984, Torday & Dow 1984, Warburton et al 1988, Romaguera et al 1993, Gilbert et al 2001, van Tuyl et al 2004. In particular, thyroid hormones promote synthesis of surfactant proteins B and C. They also increase the phospholipid content of lung liquid, although this effect may be mediated via upregulation of pulmonary b-adrenergic receptor expression and, hence, enhanced epinephrine-stimulated surfactant release (Das et al 1984, Warburton et al 1988.…”
Section: The Lungs and Respiratory Functionmentioning
confidence: 99%
“…Male fetuses present a transient delay in lung maturation compared with female fetuses (Nielsen & Torday 1981, Torday & Dow 1984, Nielsen 1985 in such a way that preterm delivery leads to a higher incidence of respiratory distress syndrome (RDS or hyaline membrane disease) in males (Farrell & Avery 1975, Papageorgiou et al 1981, Nielsen et al 1982, Perelman et al 1986a. Surfactant deficiency is one major cause of RDS and the surge of surfactant synthesis is normally delayed in the developing male lung when compared with the female (Nielsen & Torday 1981, Torday & Dow 1984, Nielsen 1985.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactant deficiency is one major cause of RDS and the surge of surfactant synthesis is normally delayed in the developing male lung when compared with the female (Nielsen & Torday 1981, Torday & Dow 1984, Nielsen 1985. In fact, the sex difference in surfactant production pertains to its lipid moiety (Nielsen et al 1982, Nielsen 1985, Ballard 1989.…”
Section: Introductionmentioning
confidence: 99%
“…A sexual dimorphism in fetal pulmonary surfactant production has been described (1)(2)(3); it is characterized in many mammalian species by an increase in female fetal surfactant phosThis work was presented in part as an abstract at the annual meeting of the Society for Pediatric Research, May 1983. Received for publication 21 September 1984 and in revised form 5 March 1985. pholipid production. This has been implicated in the clinical observations of greater incidence of the respiratory distress syndrome (RDS)' in male newborns and the failure of male fetuses to respond to prenatal glucocorticoid therapy to protect against RDS (1,4).…”
Section: Introductionmentioning
confidence: 99%